Comparative molecular dynamics simulation of apo and holo forms of the P53 mutant C176F: a structural perspective - R. Hephzibah Cathryn; C. George Priya Doss (Journal of Taibah University for Science)
Zinc fingers represent a highly diverse structural domain, with P53 being a notable example among zinc-dependent transcription factors. The folding patterns of proteins in the cell are heavily influenced by the concentration of zinc. The potential for zinc loss arises due to its dysregulation and the frequent occurrence of tumorigenic P53 mutations. This could lead to significant consequences such as protein misfolding and a reduction in tumor-suppressing capabilities. To gain deeper insights into the structural conformation, stability, flexibility, and compactness of the zinc-binding mutation C176F, a comprehensive comparative computational analysis was conducted on the wildtype (WT) and mutant (MT) P53 in the presence (Holo) and absence (Apo) of zinc. This analysis was performed using molecular dynamic simulation. The overall observation was that the mutation in C176F reduces the metal binding affinity and results in less stability in the Apo and Holo P53 MT protein.